Leprosy: An Overview of Pathophysiology - Ramesh Marne Bhat; Chaitra Prakash (Interdisciplinary Perspectives on Infectious Diseases)
Leprosy, also known as Hansen’s disease, is a chronic infectious disease caused by Mycobacterium leprae, a microorganism that has a predilection for the skin and nerves. The disease is clinically characterized by one or more of the three cardinal signs: hypopigmented or erythematous skin patches with definite loss of sensation, thickened peripheral nerves, and acid-fast bacilli detected on skin smears or biopsy material. M. leprae primarily infects Schwann cells in the peripheral nerves leading to nerve damage and the development of disabilities. Despite reduced prevalence of M. leprae infection in the endemic countries following implementation of multidrug therapy (MDT) program by WHO to treat leprosy, new case detection rates are still high-indicating active transmission. The susceptibility to the mycobacteria and the clinical course of the disease are attributed to the host immune response, which heralds the review of immunopathology of this complex disease.